1965
DOI: 10.1042/bj0970723
|View full text |Cite
|
Sign up to set email alerts
|

The molecular structure of bacterial walls. The size of ribitol teichoic acids and the nature of their linkage to glycosaminopeptides

Abstract: 1. Ribitol teichoic acids prepared by fractional precipitation of trichloroacetic acid extracts of bacterial cell walls are essentially undegraded and have similar chain length to the teichoic acid originally present in the walls. 2. The chain length of teichoic acid can be determined directly, without prior extraction from the wall. Accurate values have been obtained by measurement of the formaldehyde produced by oxidation of walls with periodate. Less accurate values have been derived from the amount of inor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

1966
1966
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Similar results with other organisms were reported by Armstrong, Baddiley & Buchanan (1960) and Hay et al (1965). Thus in lactobacilli the teichoic acid is made up of 7-6 units, in staphylococci of 8.1 and in B. subtilis of 8.9 units.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results with other organisms were reported by Armstrong, Baddiley & Buchanan (1960) and Hay et al (1965). Thus in lactobacilli the teichoic acid is made up of 7-6 units, in staphylococci of 8.1 and in B. subtilis of 8.9 units.…”
Section: Discussionsupporting
confidence: 78%
“…Thus in lactobacilli the teichoic acid is made up of 7-6 units, in staphylococci of 8.1 and in B. subtilis of 8.9 units. It seems very probable that in B. megaterium the chain of a ro-unit teichoic acid is attached to the mucopeptide by one phosphate group (phosphoramidate linkage according to Hay et al 1965) and the other group lies free on the surface, so contributing to the negative charge of the cell wall (Rogers, 1962). There is no direct evidence for this idea from our sections.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of phosphorus present in the complex is therefore more than enough to account for the attachment ofthe teichuronic acid chains to mucopeptide. Teichoic acids extracted from walls of several organisms by alkali have been shown to carry terminal phosphate groups that presumably originated from the phosphodiester linkages to mucopeptide (Hay et al 1965;Archibald, Coapes & Stafford, 1969). In this situation any residual phosphorus found to be associated with the mucopeptide after a complete extraction of teichoic acid with alkali could arise only from a source other than the teichoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that covalent linkages exist between the teichoic acids and polysaccharides of several bacterial cell walls and the mucopeptide component (Knox & Hall, 1965; Hay, Archibald & Baddiley, 1965;Button, Archibald & Baddiley, 1966;Munoz, Ghuysen & Heymann, 1967;Knox & Holmwood, 1968). In an earlier study (Hughes, 1965) of the cell wall of Bacillus licheniformis N.C.T.C.…”
mentioning
confidence: 99%
“…The actual anatomical relationship of ribitol teichoic acid to the mucopeptide of the staphylococcal cell wall is still open to speculation. It has been suggested that teichoic acid is covalently linked through the terminal phosphate group to the mucopeptide (Ghuysen, Tipper & Strominger, 1965;Hay, Archibald & Baddiley, 1965). However, such linkages do not preclude the possibility that the teichoic acid is present on the surface of the cell as a layer over the mucopeptide.…”
Section: Discussionmentioning
confidence: 99%